Conceptual retrieval for unique entities does not require proper names. Issue 2 (7th February 2023) - Davidson, Whitney; Boulais, Brooke; Tranel, Daniel; Belfi, Amy M.
ABSTRACT: When asked to describe unique entities by providing specific, identifying information, people typically include proper names for other, related concepts (e.g. song titles when describing a musician). Here, we investigated whether proper names are necessary to accurately describe famous persons and places. Participants (healthy adults, N = 39) were shown names of famous persons or landmarks and asked to provide uniquely-identifying information about each, without using proper nouns. Their performance was compared to individuals who were unrestricted in proper noun use in this task. The current participants, who were prevented from using proper names, performed similarly to comparison participants who could use proper names. Additionally, the current participants performed significantly better than participants with damage to the left temporal pole (who have impaired proper noun retrieval due to their brain damage). These findings indicate that retrieval of proper nouns is not necessary to correctly identify and define semantically unique entities.